Novel Pre-oxidation Patterning on Thin Aluminium Film Generating Ordered Nanopores through Anodization - HOLMES, JUSTIN DEREK; CROSS, GRAHAM (My University, 2010)
Anodic Aluminum Oxide (AAO) is widely employed as a template for fabrication of nanowires and nanotubes due to its ability to generate self organized (SO), well ordered pore structures. We have developed a new aluminum pre-patterning technique to create well ordered nanopore arrays on thin films deposited on silicon substrates. We form patterns of thicker oxide on the surface via local oxidation process using a conducting Atomic Force Microscope (AFM) tip working in contact mode. Pores are forced to nucleate between the pre-oxidized regions during the anodization process. The relation between applied voltage and ordered interpore distance has been found to be linear for these supported thin films. However, the pore spacing is highly reduced compared to free standing foils. A new empiric law has been confirmed for a wide range of voltages, solution concentrations and different electrolytes, including oxalic and phosphoric acid. Our results show that pre-oxidation patterning is an alternative technique to achieve an ordered nanoporous template through the anodization process.
PUBLISHED
Keywords: Condensed matter physics; Thin films